KEPEMIMPINAN VISIONER KYAI DALAM MEWUJUDKAN SANTRI YANG BERDAYA SAING DI PONDOK PESANTREN AL-BIDAYAH JEMBER - Wahyono, Imam; Fanani, Ahmad Aziz (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This study aims to describe the visionary leadership of kyai with a portrait of the role of kyai as a direction seter, change agent, spokesperson and as coach. Through this role, it is hoped that the competitiveness of students at the Al-Bidayah Jember Islamic boarding school is in accordance with the needs of the community in the future. This research was carried out because of the lack of research in Islamic boarding schools with the use of visionary leadership types but focused on the competitiveness of students. This research method uses qualitative research with a type of descriptive qualitative research. The subject of this study was a caregiver of Islamic boarding school named Dr. KH. Abdul Haris, M.Ag. Data collection techniques are in-depth interviews, observation and documentation. Data analysis techniques use Miles & Huberman theory, while data validity uses triangulation. The results of this study can be described that in carrying out his role, a kyai always involves stakeholders in formulating policies guided by the needs of the community and the future, innovating so that his vision and mission can be realized this is done by making an accelerated method in learning the yellow book and choosing the right learning methods and models, kyai socializes the vision and mission of the Islamic boarding school to the general public through da'wah in the media Social and training both in schools and Islamic boarding schools and kyai become resource persons in seminars for teachers or asatidz councils both in schools and Islamic boarding schools.